MiR-377-dependent BCL-xL regulation drives chemotherapeutic resistance in B-cell lymphoid malignancies. Issue 1 (December 2015) - Al-harbi, Sayer; Choudhary, Gaurav; Ebron, Jey; Hill, Brian; Vivekanathan, Nagarajavel; Ting, Angela; Radivoyevitch, Tomas; Smith, Mitchell; Shukla, Girish; Almasan, Alex
Abstract Background BCL-xL is an anti-apoptotic BCL-2 family protein that inhibits apoptosis and is overexpressed in many cancers. We have reported that acquired resistance to the BCL-2 inhibitor ABT-199 (venetoclax) is associated with increased BCL-xL expression. Yet, how BCL-xL mediates chemoresistance in hematopoietic malignancies is not clear. This finding may help in design of new strategies for therapeutic intervention to overcome acquired chemoresistance mediated by BCL-xL. Results We now show that the increased BCL-xL expression was inversely correlated with that of miR-377 in ABT-199-resistant cells. This finding was also extended to a panel of B-cell lymphoid lines and primary chronic lymphocytic leukemia (CLL) cells. miR-377 suppressed BCL-xL expression by recognizing two binding sites in the BCL-xL 3'-UTR. Mutation of these two miR-377 consensus-binding sites completely abolished its regulatory effect. Expression of a miR-377 mimic downregulated BCL-xL protein expression and significantly increased apoptotic cell death. Expression of a miR-377 inhibitor restored BCL-xL protein expression and limited cell death caused by the hypomethylating agent 5-azacytidine. Thus, miR-377-dependent BCL-xL regulation drives acquired therapeutic resistance to ABT-199. We further show that CLL patients who received a diverse array of chemotherapy regimens also had significantly higher BCL-xL and lower miR377 expression, indicating that exposure to chemotherapy might trigger transcriptional silencing of miR-377, which results in high levels of BCL-xL. Importantly, CLL patients with high BCL-xL/low miR-377 expression had an advanced tumor stage. Moreover, the high BCL-xL expression correlated with short treatment-free survival in 76 CLL patients. miR-377 is located at 14q32 in the DLK1-DIO3 region, which encodes the largest tumor suppressor miRNA cluster in humans. Examination of five additional 14q32 miRNAs revealed that the majority were significantly down-regulated in most CLL patients as well as in ABT-199-resistant cell lines. Remarkably, four of these miRNAs had significantly decreased expression in chemotherapy-treated CLL patients as compared to those untreated. These findings indicate a reduced expression of multiple miRNAs that may reflect a global silencing of this miRNA cluster in therapy-resistant lymphoid cells. Conclusions These findings reveal a novel mechanism by which down-regulation of miR-377 increases BCL-xL expression, promoting chemotherapy resistance in B-cell lymphoid malignancies.